Enhancing conservation of Australian freshwater ecosystems: identification of freshwater flagship fishes and relevant target audiences. Issue 4 (27th April 2016) - Ebner, Brendan C; Morgan, David L; Kerezsy, Adam; Hardie, Scott; Beatty, Stephen J; Seymour, Jamie E; Donaldson, James A; Linke, Simon; Peverell, Stirling; Roberts, David; Espinoza, Thomas; Marshall, Nadine; et al.
Abstract: Flagship species, especially mammals and birds, are commonly used to increase awareness of conservation issues in marine and terrestrial ecosystems. However, flagship species oriented programs are often ad hoc with initiatives scarce in the freshwater context. Here, we aim to identify potential flagship candidates that would appeal to a broad cross section of society at a continental scale where freshwater ecosystems are under threat from human impacts. We identified 19 species from a list of 299 Australian freshwater fishes on the basis of body size, trophic guild and threatened species status assuming these characteristics of flagship species are transferable from previous work on terrestrial flagship species. We considered the potential of species to be of international appeal but focused mostly on eight relevant interest groups within Australia. This followed the rationale that public engagement with conservation issues in freshwater systems might be more effective if the link between fish species and the decisions people make were better understood, and we acknowledge the diverging interests of stakeholders. This scoping work contributes towards addressing the challenges of connecting societies to the principles of sharing water resources with ecosystems, and represents the first continental‐scale assessment of its kind.